2011
DOI: 10.7150/thno/v01p0277
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of I-domain of LFA-1 to Target Drug and Marker Molecules to Leukocytes

Abstract: The long-term objective of this project is to utilize the I-domain protein for the α-subunit of LFA-1 to target drugs to lymphocytes by binding to ICAM receptors on the cell surface. The short-term goal is to provide proof-of-concept that I-domain conjugated to small molecules can still bind to and uptake by ICAM-1 on the surface of lymphocytes (i.e., Raji cells). To accomplish this goal, the I-domain protein was labeled with FITC at several lysine residues to produce the FITC-I-domain and CD spectroscopy show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 49 publications
(48 reference statements)
0
26
0
Order By: Relevance
“…122 Animal studies have tested the possibility of blocking leukocyte adhesion molecules by antibodies to reduce venous ischemic injury. 123126 More specifically, these studies have used different antibodies specific to different molecules, capable of inhibiting adhesion molecules of interest in order to prevent reperfusion injury in animal models of myocardial infarction.…”
Section: Potential Novel Therapies and Future Research Directionsmentioning
confidence: 99%
“…122 Animal studies have tested the possibility of blocking leukocyte adhesion molecules by antibodies to reduce venous ischemic injury. 123126 More specifically, these studies have used different antibodies specific to different molecules, capable of inhibiting adhesion molecules of interest in order to prevent reperfusion injury in animal models of myocardial infarction.…”
Section: Potential Novel Therapies and Future Research Directionsmentioning
confidence: 99%
“…We have shown that the fluorescence-labeled I-domain binds LFA-1 and is internalized by lymphocytes. 25 Similar to BPI molecules, IDAC conjugates are hypothesized to inhibit the immunological synapse formation during the process of T-cell activation by simultaneous binding of the PLP peptide and I-domain to MHC-II and ICAM-1, respectively, on APC. This simultaneous binding forms a bridge between the two receptors and eventually prevents the translocation and reorganization of Signal-1 and Signal-2.…”
Section: Discussionmentioning
confidence: 99%
“…As controls, I-domain and the GMB-I-domain produced slight delays of disease onset but no significant suppression of disease; this activity was probably due to the general inhibition of LFA-1/ICAM-1-mediated leukocyte adhesion. 17 In the future, the effect of injections of IDAC-3 and I-domain on the differentiation of immune cells will be evaluated. Because the therapeutic index of IDAC-3 has not been fully determined, the effect of increasing the dose while maintaining the schedule of 2 injections as well as multiple injections (greater than 3 injections) at low doses (less than 10 nmol) by spreading the injection over a longer timespan will also be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…17 The identity, purity, and secondary structure of the protein were confirmed by mass spectrometry, SDS-PAGE, and CD, respectively.…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation